Histopathological evaluation of the efficacy of carbon nanoparticle staining in detecting lymph node metastasis in colorectal cancer surgery - Qingzhao Feng; Xin Zhang; Shuyang Yang; Yingqi Feng; Hong Chen; Jiafeng Wang; Zijian Li; Shuang Fu; Qi Sun; Min Feng (Scientific Reports)
Abstract The aim of this study is to conduct a retrospective analysis on the correlation between lymph node staining and lymph node metastasis following laparoscopic radical resection of colorectal cancer using a carbon nanoparticles tracer. Additionally, the study seeks to investigate the potential clinical implications of carbon nanoparticles (CNs) in the context of colorectal cancer surgery. Clinical data was collected from patients who underwent laparoscopic radical resection of colorectal cancer at a ward of the Department of General Surgery, Nanjing Drum Tower Hospital between January 2022 and December 2023. Patients were pathologically confirmed to have primary colorectal cancer with lymph node metastasis. The patients were divided into two groups based on whether they received carbon nanoparticle suspension injection under colonoscopy prior to the operation: the carbon nanoparticles group (CNs group, n = 80) and the control group (non-CNs group, n = 39). The histological sections of all lymph nodes were reviewed, assessing lymph node staining and tumor metastasis. There were no statistically significant differences in sex, age, body mass index, operation time, blood loss, tumor location, and postoperative pathological stage between the CNs group and the control group. However, the average number of lymph nodes differed significantly between the two groups (P = 0.001). A total of 1626 lymph nodes were obtained from the CNs group. Among these, 207 were identified as metastatic lymph nodes, with 27 showing staining with carbon nanoparticles (1.66%) and 182 showing no staining (11.19%). Of the remaining 1417 normal lymph nodes, 787 were found to be stained with carbon nanoparticle (48.4%) while 630 were not. Out of the 80 patients in the CNs group, none exhibited staining solely in metastatic lymph nodes, 56 patients (70%) did not exhibit staining in either metastatic or normal lymph nodes, 19 patients (23.75%) exhibited staining in both metastatic and normal lymph nodes, and 5 patients (6.25%) did not exhibit staining in either type of lymph node. The utilization of carbon nanoparticle staining prior to laparoscopic colorectal cancer surgery has been shown to enhance the detection of lymph nodes, providing valuable assistance to surgeons and pathologists. However, the efficacy of carbon nanoparticle staining in identifying metastatic lymph nodes is limited, as non-metastatic lymph nodes may also be stained. Consequently, reliance solely on lymph node staining for precise dissection during surgery is not advisable. There is a critical need for the development of more accurate active targeting tracers.